Ancient sculpture and chiseling of woman's body in Marie Claire magazine, during the Nazi occupation of France (Palíndromo, 2025)
The article relates canonical and monumentalized sculptures from Classical Antiquity and typologies of women's bodies in the French Marie Claire, in 1940, compared to media images based on the Warburgian concern with the statal symbolic modeling. The Didi-Hubermanian notion of "critical return" allows us to observe the collision of different times involved in Marie Claire’s montages, involving reproductions of sculptures, fashion photographs, drawings and texts. We suspected that basic references from the Art History, Greco-Roman sculptures, reinforced by supposedly scientific schemes of morphological/physiognomonical studies by Alfred E. Auguste Thooris, in the early twentieth century, have points of tension between such montages of some elements of the Fascist and Nazi aesthetic projects, operated by modern media, acting as principles of Fashion. Such images would materialize model devices of standardization of the beauty and domestication of women's bodies, reporting both the Western plastic tradition and the alleged demands of the Second World War.
Keywords: French magazine Marie Claire; Symbolic modeling; Political iconography; Fashion and art history; Beauty and Mass Image